A dermatologist's ammunition in the war against smoking: a photoaging app - Brinker, Titus Josef; Enk, Alexander; Kalle, Christof von (Journal of medical internet research)
This viewpoint reviews the perspectives for dermatology as a specialty to go beyond the substantial impact of smoking on skin disease and leverage the impact of skin changes on a person's self-concept and behavior in the design of effective interventions for smoking prevention and cessation. [J Med Internet Res 2017;19(9):e326]